Toughening of epoxy novolac resin using cardanol based flexibilizers - Gour, Rajeshwari S.; Kodgire, Vivek V.; Badiger, Manohar V. (Journal of Applied Polymer Science, 2016)
In this work, two different cardanol based epoxies (Cardolite NC-514 and Cardanol NC-547) were employed as flexibilizers to toughen an epoxy novolac resin namely, poly[(phenylglycidyl ether)-co-formaldehyde] (PPGEF). 4,4-Diamino-3,3-dimethyl dicyclohexyl methane (BMCHA) was used as a curing agent. Differential scanning calorimetry and dynamic mechanical thermal analysis of the composites showed a gradual decrease in glass transition temperatures (T-g) with increase in cardolite content confirming the incorporation of flexible moieties into the brittle resin matrix. Improvement in toughening of PPGEF/Cardolite composites was manifested by increase in the izod impact strength of both the composites. The tensile strength increased marginally for composites with increasing amount of Cardolite NC-514 but decreased for the composites containing Cardolite NC-547. This was attributed to the lack of rotational motion in the chain due to close proximity of rigid phenyl rings in NC-547. SEM of the cryo-fractured surfaces of composites showed good compatibility between PPGEF and cardanol based flexibilizers. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43318.
Keywords: composites; crosslinking; glass transition